A Simplified Model for the Prediction of the Thermal Performance for Cross Flow Air Cooled Heat Exchangers with a New Air Side Thermal Correlation - Hussain Tarrad, Ali; Abdul Wahed, Ma’athe; Saad Khudor, Dhamia’a (Journal of Engineering and Sustainable Development, 2008)
This investigation deals with the performance prediction of the cross flow air cooled heat exchangers. Experimental and theoretical studies were conducted to perform the optimization of the thermal design of the heat exchanger. The experimental work was carried out by two different types and sizes of finned tube air cooled heat exchangers. An experimental rig was built for this object which provides hot water at the range of (40 to 70) Cº with water circulating rate of (200 to 1800) l/hr at absolute pressure of (2) bar. A centrifugal fan was installed as a major part of the experimental rig to provide atmospheric air with volumetric flow rate of (1250 and 2500) cfm. The performance parameters measured in the experimental work were flow rates and temperature at the entering and leaving sides of the process and service fluids passing through the heat exchanger. Further, the water side operating pressure at the inlet and exit ports, and the wet bulb temperature of air on both sides of heat exchanger have been measured as well. The entering air dry bulb and wet bulb temperatures were in the range (16 to 24) Cº and (13 to 20) Cº respectively.